A novel frameshift mutation of the ATM gene in a Chinese family with hereditary gastrointestinal tumors. Issue 1 (31st December 2022) - Sun, Gongping; Fu, Guanyu; Tang, Yuanxin; Yi, Junjie; Su, Rongjun; Liu, Wei; Lu, Xiaobo; Li, Xiaoxia
Abstract : Gastrointestinal tumor is a common malignancy that is dangerous to human health. Some of the patients exhibit familial hereditary syndromes; however, the molecular genetics of hereditary gastrointestinal tumors remain unclear. Here, a Chinese family including 21 people was investigated. Among them, three cases were respectively diagnosed with gastric cancer, colon cancer, and liver cancer; one case was diagnosed with cystic ovarian. Whole-exome sequencing (WES) and Sanger sequencing were applied to identify the pathogenic mutation of four patients. A novel frameshift mutation in exon 49 (c.7141_7151del) of ataxia telangiectasia mutated ( ATM ) gene was detected in three patients with gastric cancer, colon cancer, and cystic ovarian but absent in patient with liver cancer. This mutation was co-segregated with the disease phenotype and was predicted to be pathogenic. The deletion mutation in the ATM gene led to a frameshift mutation of the bases after ATM, ultimately causing the protein code to terminate at 2, 401st amino acids (p.N2381fs). Our results detected a novel mutation of ATM in a family with hereditary gastrointestinal tumors and expanded the mutation spectrum of ATM gene. Taken together, these findings provide vital information about the possible detection of tumor occurrence and progression, contributing towards hereditary cancer prevention and screening. Abbreviations: ATM : Ataxia telangiectasia mutated ; InDels: Insertions and deletions; NCCN: National Comprehensive Cancer Network; SNVs: Single nucleotide variations; WES: Whole-exome sequencing